2022
DOI: 10.1182/blood.2021014240
|View full text |Cite
|
Sign up to set email alerts
|

ABO O blood group as a risk factor for platelet reactivity in heparin-induced thrombocytopenia

Abstract: Heparin-induced thrombocytopenia (HIT) is an unpredictable, potentially catastrophic adverse effect resulting from an immune response to platelet factor 4 (PF4)/heparin complexes. We performed a genome-wide association study with positive functional assay as the outcome in a large discovery cohort of patients divided into three groups: (1) functional assay-positive cases (n=1269), (2) antibody-positive (functional assay-negative) controls (n=1131), and (3) antibody-negative controls (n=1766). Significant assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Although an SNP at the ABO locus was one of the 38 significant loci identified, its statistical association was not significant after Bonferroni correction for multiple testing. GWAS studies have also found significant findings relating to the ABO gene locus, including an association with heparin-induced thrombocytopenia (HIT) ( Karnes et al., 2022 ).…”
Section: Abo Blood Group Systemmentioning
confidence: 99%
“…Although an SNP at the ABO locus was one of the 38 significant loci identified, its statistical association was not significant after Bonferroni correction for multiple testing. GWAS studies have also found significant findings relating to the ABO gene locus, including an association with heparin-induced thrombocytopenia (HIT) ( Karnes et al., 2022 ).…”
Section: Abo Blood Group Systemmentioning
confidence: 99%
“…However, large genome-wide association studies did not show any major genetic risk factors other than blood group O. 10,11 Diagnostic laboratory testing is discussed later in this review; treatment recommendations are summarized in the 2018 guidelines of the American Society of Hematology. 12 Vaccination against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) represents a biomedical breakthrough against the Covid-19 pandemic that has prevented millions of fatalities.…”
Section: Hit and Vittmentioning
confidence: 99%
“…Females are at slightly higher risk than males, and some genetic polymorphisms within FcγRIIa and related signaling proteins also increase risk. However, large genome‐wide association studies did not show any major genetic risk factors other than blood group O 10,11 . Diagnostic laboratory testing is discussed later in this review; treatment recommendations are summarized in the 2018 guidelines of the American Society of Hematology 12 …”
Section: Introductionmentioning
confidence: 99%
“…Factors in uencing the risk of HIT have been of great interesting in the eld, as treatment for HIT is only actionable after the manifestation of symptoms [8]. Studies have shown genetic polymorphisms alter HIT risk [9][10][11][12][13] with the most con dent association seen in HIT associated thrombosis [14]. Other factors such as clinical setting [15], heparin formulation [16], gender [17,18], and anti-PF4/heparin antibody titers [18] have shown associations with HIT, but many risk factors show only modest increases in chances for progression to full-blown HIT.…”
Section: Introductionmentioning
confidence: 99%